Use of Figurative Language by People With Parkinson Disease to Describe "Off" Periods: Clear as Mud. Issue 4 (August 2021) - Chahine, Lana M.; Edison, Briana; Daeschler, Margaret; Siddiqi, Bernadette; Kopil, Catherine; Marras, Connie; Mantri, Sneha
Abstract : Objective: "Off" periods are characterized by the reemergence of motor and nonmotor symptoms in individuals with Parkinson disease (PD) and often negatively affect daily functioning. Individuals' experiences are diverse and may be difficult to articulate; figurative language is often used by patients to describe such experiences. Our objective was to understand how individuals with PD use figurative language to explain off periods and how experts interpret such expressions. Methods: Individuals with self-reported PD participating in the online Fox Insight study were invited to participate in a survey about off periods. Those endorsing off periods were asked to describe their experiences with open-ended free-text responses. Instances where any type of figurative language was used were identified and classified into themes. Three movement disorder neurologists reviewed each phrase and specified what symptoms they felt were likely represented. Results: A total of 109 instances of figurative language phrases were identified across descriptions from 86 patients. Allusions to viscous materials (e.g., mud and cement) and effects of chemicals (e.g., drunkenness) were common (18.35% and 17.43% of phrases, respectively). Most phrases were interpreted by the neurologists as representing motor symptoms, but neurologists agreed on what specific symptom was being referred to for only 42 (38.5%) phrases. Conclusions: To describe off periods, individuals with PD use various forms of figurative language, but this language is not uniformly interpreted and understood by specialists. Given the subjective interpretation of figurative language, exploring what patients are trying to convey when they use such language is important and could improve patient-physician communication.